2001
DOI: 10.1128/iai.69.1.463-471.2001
|View full text |Cite
|
Sign up to set email alerts
|

Improved Innate Immunity of Endotoxin-Tolerant Mice Increases Resistance toSalmonella entericaSerovar Typhimurium Infection despite Attenuated Cytokine Response

Abstract: During infection with gram-negative bacteria, exposure of immune cells to lipopolysaccharide (LPS) from the bacterial cell membrane induces a rapid cytokine response which is essential for the activation of host defenses against the invading pathogens. Administration of LPS to mice induces a state of hyporesponsiveness, or tolerance, characterized by reduced cytokine production upon subsequent LPS challenge. In the model of experimental Salmonella enterica serovar Typhimurium infection of mice, we assessed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
101
0
4

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(110 citation statements)
references
References 46 publications
5
101
0
4
Order By: Relevance
“…Chronic MDP treatment did not affect cell viability or S. typhimurium uptake (data not shown). Bacterial killing differences of these magnitudes are seen following PRR ligand and cytokine stimulation of macrophages and other cells (7,24,32,49,52) and can, in some cases, contribute to dramatic differences in survival and disease susceptibility (49,52,55,56). Leu1007insC Nod2 homozygote/compound heterozygote MDM show trends toward decreased S. typhimurium clearance, even at baseline (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Chronic MDP treatment did not affect cell viability or S. typhimurium uptake (data not shown). Bacterial killing differences of these magnitudes are seen following PRR ligand and cytokine stimulation of macrophages and other cells (7,24,32,49,52) and can, in some cases, contribute to dramatic differences in survival and disease susceptibility (49,52,55,56). Leu1007insC Nod2 homozygote/compound heterozygote MDM show trends toward decreased S. typhimurium clearance, even at baseline (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Some investigators have postulated that the suppressed cytokine response observed in the tolerant host will result in impaired antimicrobial immunity. However, recent reports have shown that LPS-tolerant mice are more resistant to systemic infection with Cryptococcus neoformans or Salmonella enterica serovar Typhimurium (19,28). LPS tolerance has clinical relevance because the changes in immune function observed in this model parallel those seen following sepsis, major trauma, thermal injury, and high-risk surgery (1,2,8).…”
Section: Endotoxin (Lipopolysaccharide [Lps]mentioning
confidence: 92%
“…It has been reported that LPS pretreatment improves the clearance of bacteria and fungi in infection experiments (14,20) and increases survival in cecal ligation and puncture-induced sepsis (5,24) and in colon ascendens stent peritonitis (7). Therefore, it is highly expected that UT12 will result in FIG.…”
Section: Ut12 Induces Long-term Lps Tolerance In Vivomentioning
confidence: 99%
“…This phenomenon is called LPS tolerance and is defined as the reduced capacity of the host or cultured macrophage/monocyte to respond to LPS following initial stimulation (6,26). It has also been reported that bacterial or fungal removal is improved during the tolerant state, despite attenuated cytokine production (14,20). Therefore, LPS tolerance is regarded as a reasonable response that simultaneously manages both the clearance of pathogens and host protection from excess inflammation.…”
mentioning
confidence: 99%